Entre manicômios e o cuidado em liberdade: as estratégias de desinstitucionalização nos municípios de Campinas- SP e São Paulo- SP - Conceição, Maycon Leandro da (Universidade Federal de São Carlos, 2025)
This thesis aims to analyze the Mental Health, Alcohol and Other Drugs Policy, with an emphasis on the experiences of deinstitutionalization strategies for people discharged from psychiatric hospitals, Psychiatric Custody and Treatment Facilities (ECTPs) such as Psychiatric Custody and Treatment Hospitals (HCTPs) or Psychiatric Treatment Wards (ATPs) and currently from Therapeutic Communities. We start from the reflection on how public mental health policies are experienced in the daily life of services, based on the experiences of workers and users in the process of deinstitutionalization. To this end, I conducted an ethnographic study, with semi-structured interviews with workers and participant observation in the services that make up the Psychosocial Care Network (RAPS), in the cities of Campinas -SP and São Paulo -SP. It is concluded that there are inequalities in access and in the guarantee of rights; conflicts related to the social inclusion of inmates leaving psychiatric hospitals; political-institutional changes that point to a movement towards psychiatric hospitalization, fueled by Therapeutic Communities; in addition to the precariousness of work under neoliberal hegemony and the challenges of overcoming psychiatric practices in extra-hospital services.
Between mental hospitals and care in freedom: deinstitutionalization strategies in the cities of Campinas- SP and São Paulo- SP
Keywords: Desinstitucionalização; Políticas públicas de saúde mental; Reforma psiquiátrica; Movimento da luta antimanicomial; Resistência antimanicomial; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS